Protocol for performing pooled CRISPR-Cas9 loss-of-function screens - Alyssa J. Mathiowetz; Melissa A. Roberts; David W. Morgens; James A. Olzmann; Zhipeng Li (STAR Protocols, 2023)
Summary: Phenotypic screens involving pooled CRISPR-Cas9 libraries offer a powerful, rapid yet affordable approach to evaluate gene functions on a global scale. Here, we present a protocol for performing pooled CRISPR-Cas9 loss-of-function screens to identify genetic modifiers using either fluorescence-based or cell death phenotypic readouts. We describe steps for designing and amplifying the library and generating and screening cells. We then detail deep sequencing and statistical analysis using cas9 High Throughput maximum Likelihood Estimator.For complete details on the use and execution of this protocol, please refer to Bersuker et al. (2019),1 Li et al. (2022),2 and Roberts et al. (2022).3 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.